Dye Sensitized Solar Cell (DSSC) Efficiency Derived from Natural Source - Muhammad Fajri Maulana; Elvan Yuniarti; Ai Nurlaela; Sitti Ahmiatri Saptari (Jurnal Fisika dan Aplikasinya, 2021)
Dye Sensitized Solar Cell (DSSC) with natural dye from Leunca fruit (Solanum Nigrym L) and Jamblang fruit (Syzygium Cumini L) extract as sensitizer has been created. This DSSC is composed of ZnO doping TiO2 using milling tool for 30 minutes which would be used as photoelectrodes. This study used two natural dyes which are Leunca and Jamblang fruit. The characterizations were performed to examine crystal structure of ZnO-TiO2 with XRD, to measure ZnO-TiO2 particle size with SEM, to examine optical properties from the dye using UV-Vis spectrophotometer, and to run an electrical test to find the efficiency from DSSC. The results indicate that the use of Jamblang fruit as sensitizer is better than Leunca fruit. This is because Jamblang fruit extract has light absorption area on the range of 250 - 800 nm which is higher absorbance than that of Leunca fruit. In addition, the milling time applied was found to be not long enough to produce semiconductor with smaller crystal size. The electrical test result shows Jamblang fruit based DSSC performance is better than Leunca fruit. The maximum power output values are 4.01 x 10−8 Watt with the efficiency of 22.57 x 10−4 % and 2.16 x 10−7 Watt with efficiency of 6.02 x 10−4 % when radiated with Halogen lamp and sunlight, respectively. Aside from the fact that the preparation technique is relatively easy, natural dye material can be found abundantly in nature and its price is also cheap, hence this study is very promising. However, several changes are needed to gain better results. The brief of this research is to develop alternative energy from solar energy, so that its use can be maximized as environmentally-friendly energy source.